Logistics management in a handicrafts store in the district of San Martin de Porres, 2023 - Baldeón-Mestanza, Olga; De La Cruz-Puga, Anali; Meneses-Claudio, Brian; Zarate-Ruiz, Gustavo (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The objective of this research is to analyze the impact of logistics management in a handicraft store in the district of San Martin de Porres, 2023.To achieve the objective the methodology used was to conduct a qualitative research approach, basic type, the scope is descriptive and the research design is a case study, for the collection of information the interview technique was used, so a guide of semi-structured questions which was directed to 6 participants who work in the areas where the study is being conducted, also had the opinion of a specialist and as a theoretical basis we have the various scientific sources obtained from reliable sites such as Scopus, Redalyc among others.The conclusion obtained is that there is an impact of logistics management in a handicraft store because it is strongly linked to the availability of the merchandise and if this management is not done properly, it generates cost overruns due to the deterioration of the products because they are not in the right place, dissatisfied customers when the staff does not find the product or because the stock is exhausted or they do not manage to see all the products.